Penerapan Kombinasi Metode Simple Additive Weighting (SAW) dan Rank Order Centroid (ROC) dalam Keputusan Pemberian Kredit - Silvilestari Silvilestari (STMIK Budi Darma, 2019)
Lending is a very important process for credit managers. Incorrect in making decisions for credit recipients will result in failure in payment of credit bills. In order for decisions made by credit managers to be more precise, a decision support system (DSS) is needed in their calculations. In this study, the authors used a combination of Rank Order Centroid (ROC) and Simple Additive Weighting (SAW) methods in producing final preference values that are useful in ranking the judicial decisions of potential credit customers. The results of the study will provide the final value that can help credit managers in the effectiveness of credit recipient decisions.